Procedure for Providing Financing without Collateral with Wakalah Wal Murabahah Contracts at Btpn Syariah Surabaya - Yunita Kusmanningrum; Rinda Tri Wahyuni; Shalasiah Shalasiah (Majapahit Journal of Islamic Finance and Management, 2022)
In the last five years, BTPN Syariah has continued to show progress, from year to year the assets owned have continued to increase accompanied by an increase in disbursed financing. Nevertheless, BTPN Syariah was able to reduce the NPF to below 2.5% with the disbursed financing being at 10 trillion, even though the disbursed financing is collateral-free financing and is given to pre/prosperous communities. The purpose of this study is to find out and understand what kind of procedures are applied to this collateral-free financing. The method used in this research is a descriptive qualitative method with the type of field research (field research), the collection technique used is observation and in-depth interviews.